KhetScore: Impacts of using digital technologies to unlock credit and insurance for marginal farmers in Odisha - Kramer, Berber; Pattnaik, Subhransu; Ward, Patrick S.; Ganta, Tharakeswar (International Initiative for Impact Evaluation, 2025)
This brief discusses the findings of an impact evaluation of KhetScore, an innovative tool that employs digital technologies to unlock credit and insurance for small and marginal farmers in the state of Odisha, India. In the treatment group, where Dvara E-Registry offered loans and insurance based on the KhetScore methodology, farmers (particularly women) were more likely to obtain insurance and formal credit, without substituting away from informal borrowing. Despite this increase in borrowing, households in the treatment group were much less likely to report difficulty in repaying loans, which suggested favorable loan terms that eased the burden of repayment. There were beneficial effects on agricultural revenues and profits. Women in the treatment group experienced significant improvements in empowerment within the household and in their subjective mental health (specifically, reduced feelings of stress).